Kesesuaian Hubungan Antara Jenis Pompa, Sumber Air, dan Tanaman yang Dialiri - Abi Prabowo; Bambang Prastowo; I.U. Firmansyah; R.H. Anasiru (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
The research was conducted at Belawa, Wajo, South Sulawesi during dry season 011994/1995. Furrow irrigation system was used on the research. Axial type pumps were used to lilt water from creek at depths of 2 m, whereas centrifugal type pumps lifted water from the shallow well groundwater at depths of 15 m. Both type of pumps were used to irrigate soybean and maize crops with the total area for each plot of 500 m2. Maize and soybean were irrigated using furrow. Axial pump diameters and engine powers during the research were the following: 4